Therapeutic antitumor efficacy of tumor-derived autophagosome (DRibble) vaccine on head and neck cancer - Su H (Dove Medical Press, 2015)
Hang Su,1,* Qiong Luo,2,* Hao Xie,3 Xiaofeng Huang,1 Yanhong Ni,1 Yongbin Mou,1 Qingang Hu1,4 1Center Laboratory of Stomatology, Stomatological Hospital Affiliated Medical School, 2State Key Laboratory of Pharmaceutical Biotechnology, School of Life Sciences, Nanjing University, 3Institute of Life Sciences, Key Laboratory of Developmental Genes and Human Disease, Southeast University, Nanjing, People’s Republic of China; 4Leeds Dental Institute, Faculty of Medicine and Health, University of Leeds, Leeds, UK *These authors contributed equally to this work Purpose: Vaccines play important roles in antitumor biotherapy. Autophagy in tumor cells plays a critical role in depredating proteins, including tumor-specific antigens and tumor-associated antigens. We aimed to induce and collect tumor-derived autophagosomes (DRibbles) from tumor cells as a novel antitumor vaccine by inhibiting the functions of proteasomes and lysosomes.Materials and methods: DRibbles were prepared and their morphological and autophagic properties characterized. Dendritic cells (DCs) generated from the bone marrow monocytes of mice were cocultured with DRibbles, then surface molecules of DCs and B cells, as well as apoptosis of DCs, were determined by flow cytometry. Meanwhile, functional properties of the DRibble-DCs were examined by mixed lymphocyte reactions and animal experiments.Results: The diameter of autophagic nanoparticles with spherical and double-membrane structure was between 200 nm and 500 nm. DRibbles resulted in the upregulation of costimulatory molecules CD40 and CD86 as well as major histocompatibility complex (MHC)-I molecules on DCs, but not MHC-II. The expressions of CD40, CD80, and CD86 and that of MHC-II molecules on B cells were also upregulated. Moreover, suppression of tumor growth and lifetime prolongation was observed in DRibble-DC-vaccinated tumor-bearing mice.Conclusion: Our results demonstrate that naïve T cells can be activated effectively by DC cross-presenting antigens on upregulated MHC-I, suggesting that DRibbles be deployed as an effective antitumor vaccine for head and neck cancer immunotherapy in clinical trials. Keywords: autophagy, nanoparticles, dendritic cells, antitumor immunity, head and neck cancer